Effect of fetoscopic laser surgery on the placental characteristics and birth-weight discordance of twins with twin-to-twin transfusion syndrome - Wang, Xueju; Li, Luyao; Yuan, Pengbo; Zhao, Yangyu; Wei, Yuan (Frontiers in Medicine, 2022)
Objective This study explored the effect of fetoscopic laser surgery on the placental structure and birth-weight discordance of twin-to-twin transfusion syndrome (TTTS). Methods A retrospective cohort study was conducted in TTTS patients who were admitted to the Peking University Third Hospital between April 2014 and April 2020. The patients were divided into two groups: laser group and control group. Placentas with twin survival were injected, and pregnancy outcomes and placental characteristics of the two groups were compared. The correlation between the birth-weight discordance and placental characteristics in each group was analyzed. Results The gestational age at first diagnosis in the laser group was significantly smaller than that in the control group (21.6 ± 2.8 weeks vs. 27.7 ± 3.0 weeks, p < 0.001). The proportion of patients with TTTS stage-I in the laser group was significantly lower than the control group (9.4 vs. 64.0%, p < 0.001). The gestational age at delivery in the laser group was significantly larger than that in the control group (33.6 ± 2.1 weeks vs. 31.4 ± 2.5 weeks, p = 0.001). In the laser group, the birth-weight discordance ratio was positively correlated with the placental territory discordance ratio (Spearman coefficient = 0.556; p = 0.001). Conclusion The birth-weight discordance is positively correlated with placental territory discordance in TTTS patients after FLS.